(untitled) (Ustozlar uchun, 2026)
Uzbek culture represents a unique synthesis of ancient traditions, Islamic values, and influences from the Silk Road civilizations. It reflects centuries of historical development shaped by nomadic and settled lifestyles, diverse ethnic interactions, and rich artistic heritage. Traditional customs, family values, national holidays, cuisine, music, crafts, and architecture remain significant elements of cultural identity in modern Uzbekistan. Preserving and promoting cultural heritage plays an important role in strengthening national consciousness and intercultural dialogue in the contemporary globalized world.